A multipurpose panel of microhaplotypes for casework. (December 2022) - Kidd, Kenneth K.; Pakstis, Andrew J.; Gandotra, Neeru; Scharfe, Curt; Podini, Daniele
Abstract: Microhaplotypes (MHs) are SNP-based multiallelic loci that have several advantages over individual SNPs and short tandem repeats (STRs). For several years we have been searching for better MHs based on the effective number of alleles at a locus (Ae ) and the locus informativeness for population relationships (In ) with thoughts of incorporating MHs into casework. We genotyped a multiplex of our best 90 MHs on 79 populations. We have ranked the 90 by Ae and analyzed the top 24 to evaluate their potential value in forensic casework. We chose 24 to compare with the popSTR dataset of 20 CODIS markers plus four other STRs commonly typed. PopSTR has full data on 32 populations; our 24 MHs have full data on 79 pops. We have compared the two sets of 24 loci (MH and STR) in four areas: individualization, biogeographic ancestry, kinship analysis, and mixture resolution.